Comparing the utility of lung function parameters and fractional exhaled nitric oxide in predicting lung cancer - Cao, Hongli; Chen, Xianyang; Song, Yige; Xue, Teng; Xue, Zhongwen; Zhang, Guosheng; Wang, Kun; Liu, Zijin (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
This study aimed to investigate the potential clinical factors that may be associated with the incidence of lung cancer. A total of 150 individuals were enrolled in this cohort study, of which 78 were diagnosed with lung cancer. The results of this study revealed some interesting findings. Specifically, male sex, older age, and lower BMI were found to be significantly associated with an increased risk of developing lung cancer. In contrast, several pulmonary function measures, including FEV1/FVC ratio, FVC, and FEV1, were significantly associated with a decreased risk of lung cancer. Additionally, higher levels of Feno were found to be significantly associated with an increased risk of lung cancer. These findings may be useful in developing strategies for the prevention and management of lung cancer, particularly for individuals with these risk factors. Further research is needed to validate these findings and explore the underlying mechanisms behind these associations. Overall, this study provides valuable insights into the potential clinical factors that may be associated with lung cancer incidence, and it highlights the importance of early detection and prevention strategies.